Investigation and prediction of sticking tendency, blocks formation and occasional melting of lime at HT (1300 °C) by the overburning test method. (2nd August 2021) - Vola, Gabriele; Ardit, Matteo; Sarandrea, Luca; Brignoli, Gianfranco; Natali, Claudio; Cavallo, Alessandro; Bianchini, Gianluca; Cruciani, Giuseppe
Graphical abstract: Highlights: Thermal behaviour characterization of carbonate rocks for lime production. Relevance of the overburning test method. Evaluation and classification of the so-called "sticking tendency" at 1300 °C. Guidelines for lime suitability in vertical shaft kilns. Abstract: The overburning test method was developed to simulate and predict lime densification, agglomeration, and sporadic melting at the highest potential temperature of lime kilns. These events, that belong to the so-called "sticking tendency" phenomenon, are associated to formation of crusts, occlusions, and blockages in vertical lime kilns. In this work, fifty carbonate rocks, their insoluble residues, and derived burnt products were investigated through a multianalytical approach. Four groups of rocks having different burnability were identified. In addition, three fundamental mechanisms were related to the above-mentioned phenomena: dehydration melting, solid-state, and liquid-phase sintering processes. Guidelines for raw materials suitability were outlined for designing new kilns and to check the quality control in already active plants.